Effects of Service Quality on Customer Satisfaction on Retail Business - Zumrotul Fitriyah; Mei Retno Adiwati (Future Science, 2020)
The growth of the retail business has had an impact on the economy in Indonesia. So that competition between business actors is very high and each company will try to offer an advantage they have. As is the case for retail businesses, they will be competing on how to improve the quality of their service to customers. What is offered is the completeness of the product being sold, the price, service and the structure and design of the fixed location. The purpose of this study was to test measuring the service quality variables at Annisa Minimarket. This study uses primary data obtained by distributing questionnaires to Annisa minimarket customers. The analysis technique used is PLS. Based on the results of data processing, it can be concluded that the perceived service quality factor affects (significantly) on satisfaction.